A Review of the Iris Recognition Methods Used for the Individual Authentication - Abdo, Amina A.; Lawgali, Ahmed O.; Abdalla, Mohamed (Transactions on Engineering and Computing Sciences, 2020)
The automatic iris recognition has become one of the most important techniques for authenticating the identity of individuals. The analysis of human iris is a reliable tool for the individual authentication due to the iris structure. Iris patterns constitute one of the uniqueness, permanence, and performance biometric traits. Moreover, the iris is considered as not easily tampered biometric traits. Therefore, this paper considers investigating the common automated methods of iris recognition. It surveys the development of utilizing iris images as an authentication means through the explanation of the historical improvement of the processes of the iris analysis. The contribution of this paper is to provide readers with huge information collected and discussed from more than 40 papers of iris recognition studies which have been published in a period of more than 20 years.